Sporozoite and liver stage antigen plasmodium falciparum peptides bind specifically to human hepatocytes (2004)
Sporozoite and Liver Stage Antigen (SALSA) sequence synthetic peptides were used in HepG2 cell binding assays to identify regions involved in parasite invasion. SALSA 20608 () and 20611 () peptides were determined as having high binding activity in HepG2 cell assays, some of them were located in immunogenic regions. Immune-fluorescence antibody test with 24276 (20608 peptide analogue, CGIWSKDEKAQGEESHCG) showed sporozoite and merozoite reactivity. This data suggests SALSA high activity binding peptides’ (HABPs) possible role in hepatic cell invasion and merozoite invasion of erythrocytes.